ANALISIS PENERAPAN HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) PADA PROSES PRODUKSI ORIFLAKES DI PT SERELIA PRIMA NUTRISIA, YOGYAKARTA: Analysis the Application of Hazard Analysis Critical Control Point (HACCP) in The Oriflakes Production at PT Serelia Prima Nutrisia, Yogyakarta - Anim Mafaza; Ika Dyah Kumalasari (Universitas Darussalam Gontor, 2022)
PT Serelia Prima Nutrition is a food industry that makes cereals with arrowroot starch as raw material, so it is necessary to apply the HACCP system to ensure food quality and safety in the food industry. Because HACCP is a system that can control a hazard, so it can guarantee the safety of a product. This study was conducted to determine the use of HACCP and detect CCP in arrowroot cereal production at PT Serelia Prima Nutrition. This qualitative study collects data through direct observation and interviews with Quality Control personnel, as well as literature study. The results showed that there were five critical control points (CCP) in the milling, curing, mixing, weighing, and packing processes. during the mixing phase. The implementation of HACCP (Hazard Analysis Critical Control Point) in cereal production at PT Serelia Prima Nutrition has been running smoothly with documentation and records, such as monitoring forms for each stage of the process.